Application of egg white hydrolysate (EWH) to improve frothing functionality of pasteurized liquid egg in large quantity production. Issue 1 (January 2023) - Huang, Ping-Hsiu; Hazeena, Sulfath Hakkim; Qiu, Yi-Ting; Ciou, Jhih-Ying; Hsieh, Chang-Wei; Shih, Ming-Kuei; Chen, Min-Hung; Hou, Chih-Yao
Abstract: Sterilized Liquid Eggs (SLE) are convenient for the baking process by minimizing the food safety risks of fresh eggs. Although these advantages were encouraging, the thermal effects of the pasteurization process had a negative impact on the functionality of the egg whites, thus making them unattractive to the food industry. Therefore, our previous study found that adding 1–5% egg white hydrolysate (EWH) contributed to the foaminess and stability in SLE. This primary purpose of this study was to confirm the feasibility of applying the optimum concentration of EWH for simultaneous evaluation and shelf life for batch production of SLE. The physical characteristics of the foam were analyzed by adding 1 ± 0.2% of EWH to SLE, and it was found that the foam with 1% EWH had better stability (low drainage), better viscosity, and similar distribution of foam bubbles size in the microstructure. No Salmonella infection has been found during the shelf life of 7 days. In addition, the highest overall acceptability has obtained using the large quantity produced SLE with 1% EWH to produce spoon cookies, followed by sensory evaluation. The cross-sectional height of the cookie and the distribution of holes in the structure were in line with those of the non-sterilized liquid egg white (NSLE). Hence, adding 1% EWH was found to the optimum concentration, which provides good foaming performance and stability of SLE. This study conveys a positive assessment to SLE producers and potential users, as it will increase their profitability economically while meeting the market challenges.